2011
DOI: 10.1177/0267659111408997
|View full text |Cite
|
Sign up to set email alerts
|

Innominate truncal dissection and rupture into right pleural cavity following acute type A dissection of the aorta with right coronary ostial avulsion and inferior STEMI

Abstract: An innominate truncal dissection and rupture into the right pleural cavity with massive hemothorax is the initial presentation in this 66-year-old lady with type A dissection of the aorta complicated by right coronary ostial avulsion and inferior STEMI. She underwent supracoronary interposition graft replacement of the ascending aorta and hemiarch, interposition graft replacement of the innominate trunk and saphenous vein bypass grafting of the right coronary artery successfully. Innominate truncal rupture fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…4) Innominate artery dissection in acute type A aortic dissection is associated with neurological complication, but hardly ever complicated by rupture. Kaul P. et al 5) reported an innominate truncal dissection and rupture into the right pleural cavity following acute type A aortic dissection as a previously undescribed instance.…”
Section: Discussionmentioning
confidence: 99%
“…4) Innominate artery dissection in acute type A aortic dissection is associated with neurological complication, but hardly ever complicated by rupture. Kaul P. et al 5) reported an innominate truncal dissection and rupture into the right pleural cavity following acute type A aortic dissection as a previously undescribed instance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 30% of patients with ascending aortic dissection died within 24 hours and a further 50% within 48 hours, mostly due to ascending aortic rupture into pericardial or pleural cavities or mediastinum [23]. This difference, in frequency of rupture between aorta and innominate artery, is explained by Laplace’s law as well as the extrapericardial location of the innominate artery, and the support provided by the supraaortic tissues making it resistant to rupture, despite high incidence of innominate involvement in type A dissection [24]. Post traumatic innominate artery rupture has been reported after repair of type A dissection [25], as has been a rupture of innominate artery associated with a localised acute dissection, repaired with a bifurcated prosthetic graft without cerebral complications [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if right axillary cannulation is used, an innominate dissection might first declare itself as malperfusion at institution of cardiopulmonary bypass [16]. Alternately, innominate artery dissection [17] or dissection and rupture [15] presenting as right hemispherical malperfusion might be salvageable by composite femoral and innominate artery perfusion if distal IA is intact [17] or femoral and right common carotid artery perfusion when distal IA is ruptured [15]. …”
Section: Discussionmentioning
confidence: 99%
“…All our patients, in whom sole innominate cannulation was used have required ascending aortic with or without hemiarch replacement. We have used composite innominate cannulation (with additional femoral arterial cannulation) in patients who had retrograde dissection from a descending aortic intimal tear into ascending aorta [12] and composite right common carotid artery cannulation (with additional femoral arterial cannulation) in a patient with innominate artery dissection and rupture into right pleural cavity [15]. However, the remaining description outlines the procedure we follow when the intimal tear is in ascending aorta or the inferior surface of the arch.…”
Section: Introductionmentioning
confidence: 99%